(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This study explores the electrodeposition of CdHgTe thin films using a complex electrochemical bath comprising CdCl2, HgCl2, and pre-reacted metallic tellurium in concentrated nitric acid, with acetonitrile as a complexing agent. The films are deposited on SnO2 coated glass substrates using a three-electrode system, where deposition potentials are adjusted to vary Hg content without altering bath composition. After deposition, films undergo annealing at 300°C under rough vacuum conditions, enhancing crystalline quality and X-ray diffraction peak intensity. Results show that deposition at different potentials affects film quality, with annealing mitigating deterioration observed at more negative potentials. Structural analysis reveals cubic (fcc) crystal structure with predominant (111) orientation, unaffected by annealing temperature up to 300°C. This approach offers a novel, cost- effective method to tailor CdHgTe film properties, crucial for various optoelectronic applications.